2015
DOI: 10.1001/jamaophthalmol.2015.2715
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Vitamin D Status and Age-Related Macular Degeneration by Genetic Risk

Abstract: IMPORTANCE Deficient 25-hydroxyvitamin D (25[OH]D) concentrations have been associated with increased odds of age-related macular degeneration (AMD).OBJECTIVE To examine whether this association is modified by genetic risk for AMD and whether there is an association between AMD and single-nucleotide polymorphisms of genes involved in vitamin D transport, metabolism, and genomic function. DESIGN, SETTING, AND PARTICIPANTS Postmenopausal women (N = 913) who were participants of the Carotenoids in Age-Related Eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 70 publications
(116 reference statements)
1
27
0
2
Order By: Relevance
“…43 Within the sample used for this analysis, and in the overall CAREDS cohort, 14 higher HLS and dietary LZ intake were each associated with lower serum C-reactive protein, a systemic marker of inflammation, and higher vitamin D, also related to inflammatory conditions. 4446 Protective associations between serum vitamin D, which also has anti-inflammatory properties, and AMD in women with a CC Y402H genotype 47 in this sample are described in a separate manuscript. 47 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…43 Within the sample used for this analysis, and in the overall CAREDS cohort, 14 higher HLS and dietary LZ intake were each associated with lower serum C-reactive protein, a systemic marker of inflammation, and higher vitamin D, also related to inflammatory conditions. 4446 Protective associations between serum vitamin D, which also has anti-inflammatory properties, and AMD in women with a CC Y402H genotype 47 in this sample are described in a separate manuscript. 47 …”
Section: Discussionmentioning
confidence: 92%
“…4446 Protective associations between serum vitamin D, which also has anti-inflammatory properties, and AMD in women with a CC Y402H genotype 47 in this sample are described in a separate manuscript. 47 …”
Section: Discussionmentioning
confidence: 92%
“…Both scores of bone-mineral density (in the femoral neck and in the lumbar spine) are nominally significant, suggesting a protective effect for AMD in individuals having a higher bone-mineral density. Interestingly, vitamin D deficiency was linked to incident AMD in the CARED study [115] and bone-mineral density can be increased with vitamin D supplementation [116]. Of note, neither the genetic score of serum calcium concentration nor vitamin D concentration was found to be significantly associated with AMD.…”
Section: Discussionmentioning
confidence: 99%
“…2015 124 observed a 6.7-fold increased risk of age-related macular degeneration (AMD) among women with serum 25(OH)D levels less than 12 ng/mL who also had genetic risk for AMD, and noted that previous studies had found that decreased odds of AMD are associated with high compared to low concentrations of 25(OH)D.…”
Section: Macular Degenerationmentioning
confidence: 99%